Glucagon-Like Peptide 1 Analogs and their Effects on Pancreatic Islets. (May 2016) - Tudurí, Eva; López, Miguel; Diéguez, Carlos; Nadal, Angel; Nogueiras, Rubén
Abstract : Glucagon-like peptide 1 (GLP-1) exerts many actions that improve glycemic control. GLP-1 stimulates glucose-stimulated insulin secretion and protects β cells, while its extrapancreatic effects include cardioprotection, reduction of hepatic glucose production, and regulation of satiety. Although an appealing antidiabetic drug candidate, the rapid degradation of GLP-1 by dipeptidyl peptidase 4 (DPP-4) means that its therapeutic use is unfeasible, and this prompted the development of two main GLP-1 therapies: long-acting GLP-1 analogs and DPP-4 inhibitors. In this review, we focus on the pancreatic effects exerted by current GLP-1 derivatives used to treat diabetes. Based on the results from in vitro and in vivo studies in humans and animal models, we describe the specific actions of GLP-1 analogs on the synthesis, processing, and secretion of insulin, islet morphology, and β cell proliferation and apoptosis. Trends: Although GLP-1-based drugs have been improved to have long-term effects, there are still issues surrounding their oral administration. GLP-1 analogs stimulate insulin synthesis and secretion and inhibit β cell apoptosis in rodent models. Most preclinical studies show increased β cell proliferation and mass after GLP-1 analog treatment; however, whether these effects are also seen in humans remains unclear. GLP-1 analogs reduce plasma glucagon levels, but this effect might not be exerted by a direct action on α cells.